Urban Agriculture, Forestry and Green-Blue Infrastructure as "Re-discovered Commons": Bridging Urban-Rural Interface (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
This book re-explores research topics related to the relationships between urban and rural areas during the COVID-19 pandemic period in 2020 and beyond. We revisit the roles and values of the components of agricultural lands and forestlands—as well as urban ones—from the perspective of green–blue infrastructure.